Age determination of galaxy merger remnant stars using asteroseismology - Borre, Camilla C.; Aguirre Børsen-Koch, Víctor; Helmi, Amina; Koppelman, Helmer H; Nielsen, Martin B; Rørsted, Jakob L; Stello, Dennis; Stokholm, Amalie; Winther, Mark L; Davies, Guy R; Hon, Marc; Kruijssen, Diederik; et al. (Monthly notices of the Royal Astronomical Society, 2022)
The Milky Way was shaped by the mergers with several galaxies in the past. We search for remnant stars that were born in these foreign galaxies and assess their ages in an effort to put upper limits on the merger times and thereby better understand the evolutionary history of our Galaxy. Using 5D-phase space information from Gaia eDR3, radial velocities from Gaia DR2 and chemical information from apogee DR16, we kinematically and chemically select 21 red giant stars belonging to former dwarf galaxies that merged with the Milky Way. With added asteroseismology from Kepler and K2 , we determine the ages of the 21 ex situ stars and 49 in situ stars with an average σage/age of ∼31 per cent. We find that all the ex situ stars are consistent with being older than 8 Gyr. While it is not possible to associate all the stars with a specific dwarf galaxy, we classify eight of them as Gaia-Enceladus/Sausage stars, which is one of the most massive mergers in our Galaxy’s history. We determine their mean age to be 9.5 ± 1.3 Gyr consistent with a merger time of 8-10 Gyr ago. The rest of the stars are possibly associated with Kraken, Thamnos, Sequoia, or another extragalactic progenitor. The age determination of ex situ stars paves the way to more accurately pinning down when the merger events occurred and hence provide tight constraints useful for simulating how these events unfolded.
Gesehen am 08.07.2022